Analisis kesalahan berbahasa Indonesia pada berita online tribun Pontianak - Rosmaida Ela; Gina, Deltavira; Carolin, Meirisca; Saptiana Sulastri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze errors in the use of Indonesian language in news captions on the Instagram account of Tribun Pontianak. The background of this research is based on the increasing use of social media as a medium of information delivery, which requires the use of proper and correct language. However, in practice, there are still many language errors that can affect the clarity of the information conveyed.This research uses a descriptive qualitative method. The data in this study are caption texts taken from the Instagram account of Tribun Pontianak. Data collection techniques were carried out through observation and note-taking, while data analysis was conducted through identification, classification, and description of language errors.The results show that there are several types of language errors, including spelling errors, diction errors, sentence structure errors, and ambiguity in meaning. These errors can affect the clarity of the information delivered to readers. Therefore, greater attention is needed in using proper and correct Indonesian language in online media.